ATMPH 2020
DOI: 10.36295/asro.2020.231509
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid in Dermatology

Abstract: Facial melanoses are Group of pigmentary disorders that share a common clinical feature of alteration of pigmentation over the face. These are difficult to treat and affect the DLQI of the patients. Tranexamic acid is an antifibrinolytic agent which has found to efficacious in a difficult to treat facial melanosis like melasma. It targets the vascular and pigment component of melasma providing a rapid and a sustained improvement. Various studies in different doses and routes in different dermatoses are require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…TXA is an antifibrinolytic agent that shows a positive effect on wound healing in several studies, and it showed benefits in treating skin diseases like melasma, rosacea erythema and ultraviolet induced pigmentations. 16 Although it has been discovered since 1979, 17 It has attracted the attention of dermatologists recently in the past few years to use it in a refractory, resistant disorder like melasma. It has shown promising effects in all the routes administered like topical, oral or intradermal with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…TXA is an antifibrinolytic agent that shows a positive effect on wound healing in several studies, and it showed benefits in treating skin diseases like melasma, rosacea erythema and ultraviolet induced pigmentations. 16 Although it has been discovered since 1979, 17 It has attracted the attention of dermatologists recently in the past few years to use it in a refractory, resistant disorder like melasma. It has shown promising effects in all the routes administered like topical, oral or intradermal with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pada dosis minimal, efek samping juga minimal. 5 Kontraindikasi penggunaan asam traneksamat meliputi gangguan perdarahan dan pembekuan darah, hipersensitivitas terhadap obat, buta warna, stroke, kondisi sumbatan intravaskular aktif, penyakit jantung iskemik, serta tromboemboli vena. 5 Penggunaan asam traneksamat harus dengan pemantauan ketat pada pasien penyakit kardiovaskular serta penyakit pembuluh darah otak.…”
Section: Pendahuluanunclassified
“…5 Kontraindikasi penggunaan asam traneksamat meliputi gangguan perdarahan dan pembekuan darah, hipersensitivitas terhadap obat, buta warna, stroke, kondisi sumbatan intravaskular aktif, penyakit jantung iskemik, serta tromboemboli vena. 5 Penggunaan asam traneksamat harus dengan pemantauan ketat pada pasien penyakit kardiovaskular serta penyakit pembuluh darah otak. Fungsi koagulasi meliputi prothrombin time (PT), activated partial thromboplastin time (APTT), dan parameter pembekuan darah lain harus diperiksa sebelum memulai terapi asam traneksamat.…”
Section: Pendahuluanunclassified
“…It prevents side effects and organ damage, such as kidney and bone marrow damage [5,6]. Tranexamic acid is marketed in a tablet dosage form available in strengths of 500 mg per tablet [7]. Drugs marketed must meet aspects of efficacy, quality, and safety [8].…”
Section: Introductionmentioning
confidence: 99%